The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1115/1.4025360
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinth Seal and Pocket Damper Seal High Pressure Rotordynamic Test Data

Abstract: The current centrifugal compressor design for the oil & gas market is more and more challenging, and the presence of many competitors is pushing technology towards both a casing size reduction and a rotational speed increase. The first point is leading to an increase in the number of wheels per rotor (to do the same service), and the second point is forcing to cross two or even three rotor modes (hence a higher control of rotor damping is necessary). The two points together are leading to increase the roto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…To further validate the orbit decomposition method, its prediction results are compared with the experimental data tested on the high-pressure seal test rig owned by GE Oil & Gas [17]. The test object is the labyrinth seal.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations
“…To further validate the orbit decomposition method, its prediction results are compared with the experimental data tested on the high-pressure seal test rig owned by GE Oil & Gas [17]. The test object is the labyrinth seal.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
“…Five whirl frequencies are measured with a 10,000 rpm running speed. The detailed test conditions can be found in [17].…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to the labyrinth seal, the stator surface of this seal has larger roughness and bigger damping coefficient, which contribute to reduce circumferential flow velocity in the seal, decrease seal cross stiffness, and improve rotor system stability. At present, existing damping seals include honeycomb seal [14,15], hole-pattern seal [16], and pocket damper seal [17].…”
Section: Introductionmentioning
confidence: 99%
“…The above experimental and numerical results of rotordynamic coefficients for the labyrinth seal are all assumed to be frequency-independent. However, the latest test results of Ertas et al 22 and Vannini et al 23 have demonstrated that the labyrinth seal possesses strongly frequency-dependent rotordynamic coefficients, especially for the direct stiffness and effective damping coefficients. The numerical results presented by Thorat and Childs 24 show frequency dependence of stiffness and damping coefficients of labyrinth seals when rotor speed approaching to Mach 1.…”
Section: Introductionmentioning
confidence: 99%